Prognostic Value of CXCL13, CCL11, and CCL20 Chemokines in Multiple Sclerosis - Işıl Peker; Hacer Eroğlu İçli; Belgin Mutluay; Burcu Yüksel; Zeynep Özdemir; Mesrure Köseoğlu; Aysu Şen; Dilek Ataklı; Aysun Soysal; Musa Öztürk (Biomedicines)
Objective: The course of relapsing–remitting multiple sclerosis (RRMS) is highly variable and there is a lack of effective prognostic biomarkers. This study aimed to assess the potential prognostic value of the chemokines B lymphocyte chemoattractant molecule (CXCL13), eotaxin-1 (CCL11), and macrophage inflammatory protein 3-alpha (CCL20) in RRMS. Methods: Forty-two patients with MS were enrolled, along with 22 controls, 12 of the controls were idiopathic intracranial hypertension (IIH) patients, and 10 of the controls were other neurologic diseases (OND). Chemokine levels were measured using enzyme-linked immunosorbent assay (ELISA) in serum and cerebrospinal fluid (CSF) samples. Results: No significant differences were observed among the groups in serum levels of CXCL13, CCL11, and CCL20 (p = 0.509, p = 0.979, p = 0.169, respectively). CSF CXCL13 levels were significantly higher in the OND group (p = 0.016). A PATH analysis showed CSF CXCL13 was significantly associated with new T2 hyperintense lesions on brain magnetic resonance imaging (p < 0.001), and baseline serum CCL11 levels were associated with EDSS (p = 0.030), implying its potential role in indicating neurodegenerative processes and possible progression risk. Serum CCL20 correlated with EDSS (p = 0.002) and lesion burden (p < 0.001), reflecting disease severity. Conclusions: These findings suggest that CSF CXCL13 could serve as a useful biomarker for predicting active disease in RRMS, while follow-up serum CCL11 may assist in identifying progression. Although these chemokines are not specific to MS, higher levels may signal disease activity, severity, and transition to more progressive stages.